Rex versus Epeleki of Fontem: Charge, Manslaughter (Colonial Letters and the Contact of Knowledges, 1934)
This file contains colonial court minutes and decisions on Rex versus Epeleki of Fontem: Charge, Manslaughter
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies